Hidradenitis Suppurativa: a lesser-known cause of AA amyloidosis - Helvacı, Ö (Hippokratia, 2020)
Background: Hidradenitis suppurativa (HS) is a chronic, disabling skin disease. The estimated prevalence is 1-4 % worldwide. HS is a systemic inflammatory disease and can cause AA amyloidosis. The first report of HS-related amyloidosis dates back to 1966; since then, sporadic cases have been reported. Our work will be the first case series on HS and AA amyloidosis. Case series: We report eight HS cases complicated with amyloidosis. Six patients were male. The median age was 44 years, and the median disease duration before the amyloidosis diagnosis was 15.5 years. In a mean follow-up of 18 ± 6 months, we achieved favorable renal responses in four of the eight cases (50 %). All cases had a dermatologic response, with four complete and four partial remissions. Conclusion: HS is a systemic inflammatory disorder that may cause AA amyloidosis. Aggressive treatment of HS may halt the progression of amyloidosis. HIPPOKRATIA 2020, 24(1): 33-37.